2018
DOI: 10.1016/j.juro.2017.12.061
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Outcomes of Robotic and Open Inguinal Lymph Node Dissection in Patients with Carcinoma of the Penis

Abstract: Robot-assisted video endoscopic inguinal lymphadenectomy is a feasible technique which allows for a similar nodal yield while being associated with lower morbidity than open inguinal lymph node dissection in patients without bulky groin adenopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 21 publications
5
48
0
1
Order By: Relevance
“…Estimated blood loss during RVEIL in different studies ranges from 10-200 mL and appears to be comparable to open ILND as reported by Singh and colleagues [21,23]. Russell and colleagues reported a median blood loss of 50 mL per groin in 27 RVEIL groin dissections [20].…”
Section: Peri-operative Outcomes and Complicationssupporting
confidence: 65%
See 1 more Smart Citation
“…Estimated blood loss during RVEIL in different studies ranges from 10-200 mL and appears to be comparable to open ILND as reported by Singh and colleagues [21,23]. Russell and colleagues reported a median blood loss of 50 mL per groin in 27 RVEIL groin dissections [20].…”
Section: Peri-operative Outcomes and Complicationssupporting
confidence: 65%
“…Minimally invasive techniques have primarily been described in penile cancer patients with non-palpable or small palpable lymphadenopathy. However, the use of these techniques in patients with significant palpable inguinal lymphadenopathy as well as following treatment with neoadjuvant therapy is also reported [19][20][21]. Here, we discuss utilization of these approaches including their surgical techniques, peri-operative results and complications, and oncological outcomes.…”
Section: Minimally Invasive Approachesmentioning
confidence: 96%
“…Overall, major complications are reported in 5–21% of dissections and minor complications in 40–54% of dissections . Even the modified lymph node dissections, and those performed laparoscopically or robotically, are not without severe complications .…”
Section: Discussionmentioning
confidence: 99%
“…Often, scrotal lymphedema leading to buried penis is the result of postoperative sequelae from surgeries such as pelvic lymph node dissection during prostatectomy, inguinal lymphadenectomy for penile cancer or melanoma, or aortobifemoral bypass grafting. In a series of 340 inguinal lymphadenectomies for penile cancer, early lymphedema rates of 4.1% and scrotal edema rates of 0.9% were noted ( 9 ) with late lymphedema rates ranging from 5–9% ( 10 , 11 ). In patients from developing countries, scrotal lymphedema is often seen as the genital manifestation of lymphatic filariasis, also known as elephantiasis.…”
Section: Managementmentioning
confidence: 99%